Samotolisib Attenuates Acute Liver Injury Through Inhibiting Caspase-11-Mediated Pyroptosis Via Regulating E3 Ubiquitin Ligase Nedd4 - Zhao, Yang-Yang; Wu, Dong-Ming; He, Miao; Zhang, Feng; Zhang, Ting; Liu, Teng; Li, Jin; Li, Li; Xu, Ying (Frontiers in Pharmacology, 2021)
Acute liver injury (ALI) is associated with poor survival in patients with sepsis. During sepsis, the liver is the main site of bacterial endotoxin-induced inflammation. Lipopolysaccharide (LPS) promotes caspase-4/5/11 activation, leading to pyroptosis, a major sepsis driver. This study aimed to identify novel drugs that can control hepatocyte caspase-4/5/11 activation during sepsis. We performed LPS-induced caspase-11 activation and pyroptosis in RAW 264.7 cells and established an LPS-induced ALI mouse model. We identified samotolisib (ST), a novel dual phosphoinositide 3-kinase (PI3K) and mammalian target of rapamycin (mTOR) inhibitor, by screening a library of 441 pyroptosis compounds with known targets, which dose-dependently inhibited caspase-11 activation and N-terminal fragment of gasdermin D (GSDMD-NT) generation, reducing RAW 264.7 cell pyroptosis. In mice, ST preconditioning improved survival, attenuated LPS-induced serum alanine aminotransferase and aspartate aminotransferase activity, and inhibited severe liver inflammation and damage. Importantly, ST treatment activated Nedd4, which directly interacts with and mediates caspase-11 ubiquitination and degradation. This was largely abrogated by insulin-like growth factor 1. ST ameliorated LPS-induced hepatotoxicity by inhibiting caspase-11/GSDMD-NT pyroptosis signaling via regulating PI3K/AKT/mTOR/Nedd4 signaling. Hence, ST may play a key role in the prevention of liver injury in patients with sepsis.